Disease burden of low back pain attributable to ergonomic risk factors in selected Chinese occupational groups - Fang ZHOU; Mengshuang LIU; Jiayi LAI; Kezhi JIN (环境与职业医学, 2022)
BackgroundAs traditional chemical and physical hazards as well as associated adverse health outcomes in workplace were wildly controlled in the past half century, the prevalence and disease burden of low back pain (LBP) have drawn more and more attention and become one of the important public health problems in the world. ObjectiveTo analyze the health loss and attributable disease burden of ergonomic risk factors for LBP in two major categories of occupations in China, aiming to provide evidence for formulating effective prevention and control policies of LBP in the workplace. MethodsBased on the methodological framework of the Global Burden of Disease Study (GBD), a meta-analysis was firstly applied to summarize relevant literature results and estimate the prevalence of LBP in two occupational groups (including technicians and associate professionals and machine operators and assemblers) by different age groups in China. Then important epidemiologic parameters (including disability weight, remission rate, and incidence) from GBD 2019 were used to estimate mean duration of disease and age at onset using DisMod II software, and to calculate health loss indexes in the selected occupational groups in China in 2013, such as years lived with disability (YLD) and disability-adjusted life year (DALY) of LBP and its attributable fractions by ergonomic risk factors, which were compared to the outcome of GBD 2013. ResultsAfter the adjustment by DisMod II, the prevalence rate of LBP was 13.00% in technicians and associate professionals (11.25% for males and 14.84% for females) and 14.80% in machine operators and assemblers (13.56% for males and 16.10% for females) in 2013, which increased with age. The DALY rate of LBP was 8.02‰ in technicians and associate professionals (7.68‰ for males and 8.33‰ for females) and 10.34‰ in machine operators and assemblers (10.30‰ for males and 10.44‰ for females), which also showed an overall increasing trend with age. In 2013, the population attributable fraction (PAF) of ergonomic risk factors to LBP was 11.42% in technicians and associate professionals and 29.17% in machine operators and assemblers. The DALY of LBP attributable to ergonomics risk factors was 4498 person-years (2108 person-years for males), with the highest DALY in the 45-49 year group (951 person-years), and the attributable DALY rate was 0.92‰ in technicians and associate professionals. The DALY of LBP attributable to ergonomics risk factors was 48529 person-years (33046 person-years for males), with the highest DALY in the 40-44 year group (10852 person-years), and the attributable DALY rate was 3.02‰ in machine operators and assemblers. Regarding LBP-associated DALY rate, in the 20 years of age and above group, both occupational groups (technicians and associate professionals: 8.06‰, machine operators and assemblers: 10.66‰) showed higher values than the general population (3.55‰). In the 20 years of age and above group, the DALY rates attributable to ergonomic risk factors with the order from high to low were machine operators and assemblers (3.11‰), general population (1.10‰) and technicians and associate professionals (0.92‰).ConclusionThe LBP-associated disease burden is heavier in the two Chinese occupational groups than in general population. Reducing the disease burden of LBP by interventions targeting ergonomic risk factors in machine operators and assemblers is more effective than that in technicians and associate professionals as the results of attributable burden of disease suggest.